The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.4236/jmp.2011.226071
|View full text |Cite
|
Sign up to set email alerts
|

Entropy Production Rate for Avascular Tumor Growth

Abstract: The entropy production rate was determined for avascular tumor growth. The proposed formula relates the fractal dimension of the tumor contour with the quotient between mitosis and apoptosis rate, which can be used to characterize the degree of proliferation of tumor cells. The entropy production rate was determined for fourteen tumor cell lines as a physical function of cancer robustness. The entropy production rate is a hallmark that allows us the possibility of prognosis of tumor proliferation and invasion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 13 publications
(17 reference statements)
2
36
0
1
Order By: Relevance
“…If we compare the healthy individuals with patients of both sexes for the same chronological age, we observe that people with cancer exhibit greater value the entropy production rate, which can be interpreted as that the cancer exhibits a higher robustness, an aspect that we have found in previous works. [40][41][42] Moreover, these results give a plausible explanation to the unexplained elevation of the basal metabolic rate that has previously been reported for cancer patients.…”
Section: Figurementioning
confidence: 78%
See 1 more Smart Citation
“…If we compare the healthy individuals with patients of both sexes for the same chronological age, we observe that people with cancer exhibit greater value the entropy production rate, which can be interpreted as that the cancer exhibits a higher robustness, an aspect that we have found in previous works. [40][41][42] Moreover, these results give a plausible explanation to the unexplained elevation of the basal metabolic rate that has previously been reported for cancer patients.…”
Section: Figurementioning
confidence: 78%
“…26 This evidence, gives us a plausible response to the emergence of aging processes, and allows us to postulate that they are activated through what it could be called "biological phase transition". Furthermore, although the human males exhibit greater complexity ( i S >  ) than to the females ones, which implies greater robustness, [40][41][42] it is observed that slope in healthy females from 20 to 50 years, is lower than that of males (Figure 1). It gives some stability and also robustness during the active period of the women.…”
Section: Figurementioning
confidence: 99%
“…We have recently demonstrated that the entropy production rate i S  for avascular tumor growth is related to the cancer robustness [5,18] and can be expressed as a function of fractal dimension f d as:…”
Section: Thermodynamics Approachmentioning
confidence: 99%
“…Our models suggest [22,23] that the development of a primary tumor from a microscopic level, avascular growth, to a macroscopic level, vascular phase and the subsequent appearance of metastasis, is not simply the accumulation of malignant cells, but it is a dynamic non-linear, self-organized process, far from thermodynamic equilibrium, which exhibits a high degree of robustness, complexity and hierarchy [23] and that in turn leads to the creation of new information and learning ability.…”
Section: What Can Be Learned From a Phasementioning
confidence: 99%
“…The thermodynamics formalism previously developed [10,22,23,26,27,28] suggests that the tumor that exhibit a greater value of the entropy production rate have an increased invasive ability and so they have more aggressive capacity. As a matter of fact, the entropy production rate can be the useful tool to quantify the robustness and it may be used as a quantitative index of the metastatic potential of tumors.…”
Section: What Can Be Learned From a Phasementioning
confidence: 99%